RESILIENCE CHARACTERISTICS OF FAMILIES WITH CHILDREN WITH SEVERE OR PROFOUND INTELLECTUAL DISABILITY - Dürr, Elna; Greeff, Abraham (Social Work/Maatskaplike Werk, 2020)
The aim of this study was to explore family characteristics and resources that assisted families to adapt after their children had been diagnosed with severe or profound intellectual disability. A qualitative research approach with a cross-sectional design was used, as the study was focused on participants’ experiences. It was found that spiritual resources and reformulation of the crisis helped families to reframe their experiences with a more positive outlook. Social support from the family networks, friends and the community, and positive family characteristics, such as perseverance and humour, also contributed to family adaptation and well-being. Good planning regarding daily activities, as well as for their children's future, was also deemed important.